COMPARISON OF MAX30100 BLOOD OXYGEN DETECTOR RESULTS WITH SMART WATCH - Dirja Nur Ilham; Muhammad Khoiruddin Harahap; Rudi Arif Candra; Arie Budiansyah; Herry Setiawan (LPPM Universitas Deli Sumatera, 2023)
The development of modern component technology makes it possible to create practical, compact, reliable, effective, and efficient equipment/instrumentation. The health sector as an essential component of life is also not spared from technological support. One significant indicator of oxygen supply in the body is oxygen saturation. Because oxygen saturation can show whether hemoglobin can bind oxygen or not. So that the lack of oxygen which is at risk of damage to essential organs in the body can be overcome. By using the max30100 sensor is a detection tool that will be used to detect oxygen levels with saturation levels, namely, normal and abnormal, and the tool is controlled by Arduino Nano as the controller of the entire circuit. With the output displayed on the Oled LCD, ten tests have been carried out. times and compared with the results using a Smart Watch with an average difference of 0.73%.